Peak velocity of nordic ski double pole technique - Tervo, J.; Jensen, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
One of the event styles in cross-country skiing is the classic technique in which the skis move in groomed tracks. Double poling is a technique used under the classic skiing style, and is defined as when the upper body provides most of the propulsion via bilateral pole pushes. Double poling during classic cross-country skiing has become more popular in the past twenty years. It has also been shown to have strong correlations with increased race speed (Smith, Fewster, & Braudt, 1996). Maximal velocity considers an overall velocity of the movements, but does not specify at which point during the poling phase that peak velocity occurs. By breaking a movement down into its components one may be able to critique technique more specifically. This study examined the point at which peak linear velocity occurred during the double poling cycle time in Nordic stand-up and sit-down skiing.